(untitled) (Comprehensive Journal of Science, 2025)
The term ideology is considered one of the modern or contemporary concepts that has emerged in recent times to express thought in one of its forms and its relationship with reality, whether political, social, or economic. It has led to the emergence of certain representations that differ from reality and portray it in a manner contrary to its true description. This necessitates a precise understanding of the concept of ideology, illusion and imagination.